Hydrothermal assembly of two new 3D zinc(II) pcu nets : coordination chemistry, crystal structures, and fluorescence properties - Zhu, Xiaofei (2015)
Self-assembly of zinc(II) coordination polymers have attracted intense interests due to their intriguing frameworks and fluorescence properties. Two new 3D ZnII coordination polymers with pcu networks, formulated by [Zn2L1L2(mbtz)]·H2O (1) and [Zn4L12L22(btp)2]·7H2O (2) [H2L1 = 2,5-dibenzoylterephthalic acid, H2L2 = 4,6-dibenzoylisophthalic acid, mbtz = 1,3-bis(1,2,4-triazol-1-ylmethyl)benzene, and btp = 1,3-bis(1,2,4-triazol-1-yl)propane], were synthesized under normal hydrothermal conditions. Single-crystal X-ray diffraction analyses revealed that both of the two compounds exhibited interesting 3D pcu frameworks, and showed shifted fluorescent emissions arising from the coordination chemistry between ZnII and the N-donor ligands.